Experimental investigation of dehumidification performance of a vapor compression refrigeration system - Tang, Chunli; Vafai, Kambiz; Gu, Conghui; Gloria, Kasolongo Ndongo; Karim, M.D. Razaul (International communications in heat and mass transfer, 2022)
The dehumidification performance of a vapor compression refrigeration system (VCRS) is investigated in this work, including total refrigerating capacity (TRC), total dehumidification capacity (TDC), latent heat ratio (RLH), and power consumption per unit dehumidification capacity (PCPDC). Experiments were performed for the VCRS with the rated refrigerating capacity of 7 kW. The influence of indoor air parameters including the temperature, humidity and flowrate on the dehumidification performance were studied. TDC and RLH decreased with an increase in the air temperature at a fixed humidity ratio, and increased with an increase in the air humidity at a fixed temperature. PCPDC decreased with an increase in the air humidity. The effect of the air flowrate was more complex than that of the air temperature and humidity. There was a maximum value in TDC and a minimum value in PCPDC with an increase in air flowrate for each humidity. For example, TDCmax was 2.45 kg/h for 38% rh and 6.62 kg/h for 80% rh, accordingly, PCPDCmin was 3383.48 kJ/kg for 38% rh and 1286.5 kJ/kg for 80% rh at 26 °C. As the humidity increases, the maximum and minimum values shifted towards larger flowrates. The experimental results are useful for the operation of VCRS and the design and control of convection-radiation air conditioning (CRA/C) system for the improvement of the environmental comfort.